2020
DOI: 10.1002/anie.202002774
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Insertion of Aluminum(I) in the cyclo‐P5 Ring of Pentaphosphaferrocene

Abstract: A route to directly access mixed Al-Fe polyphosphide complexes was developed. The reactivity of pentaphosphaferrocene, [Cp*Fe(h 5 -P 5 )] (Cp* = C 5 Me 5 ), with two different low-valent aluminum compounds was investigated. The steric and electronic environment around the [Al I ] centre are found to be crucial for the formation of the resulting Al-Fe polyphosphides. Reaction with the sterically demanding [Dipp-BDIAl I ] (Dipp-BDI = {[2,6-i Pr 2 C 6 H 3 NCMe] 2 CH} À ) resulted in the first Al-based neutral tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 73 publications
0
6
0
2
Order By: Relevance
“…[46] This is reminiscent of the cluster compound [(Cp*Al(IMe 4 ))(m,h 3 :h 4 -P 5 )FeCp*] with an h 1 Cp* group on aluminium, which displays an AlÀC NHC distance [2.017 (6) ] shorter than those of 5 [2.100(2), 2.083(2)]. [47] In the related compound [(IiPr 2 )HAl(m-PSiPh 2 tBu)] 2 the NHCs are in a cisarrangement. [15] Surprisingly,o ne of the ring phosphorus atoms is now in an early planar coordination environment (S(]P2) = 347.878 8), whereas the other is now closer to an ideal trigonal pyramidal coordination environment (S(]P1) = 299.838 8).…”
Section: Reactivity Of Diphosphadialanes With Lewis Basesmentioning
confidence: 99%
“…[46] This is reminiscent of the cluster compound [(Cp*Al(IMe 4 ))(m,h 3 :h 4 -P 5 )FeCp*] with an h 1 Cp* group on aluminium, which displays an AlÀC NHC distance [2.017 (6) ] shorter than those of 5 [2.100(2), 2.083(2)]. [47] In the related compound [(IiPr 2 )HAl(m-PSiPh 2 tBu)] 2 the NHCs are in a cisarrangement. [15] Surprisingly,o ne of the ring phosphorus atoms is now in an early planar coordination environment (S(]P2) = 347.878 8), whereas the other is now closer to an ideal trigonal pyramidal coordination environment (S(]P1) = 299.838 8).…”
Section: Reactivity Of Diphosphadialanes With Lewis Basesmentioning
confidence: 99%
“…Roesky and co‐workers also studied the reaction of 140 a toward related low valent aluminium compounds [73] . Treatment of 140 a with an equimolar amount of [Al(nacnac)] (nacnac=CH[CMeN(2,6‐ i Pr 2 C 6 H 3 )] 2 ) at room temperature afforded the triple‐decker type complex [(nacnacAl)(μ 2 ,η 3 :η 4 ‐P 5 )FeCp*] ( 150 a ), which features a bent cyclo ‐P 5 middle‐deck (Scheme 25 c).…”
Section: Transition‐metal‐mediated Functionalization Of White Phosphorusmentioning
confidence: 99%
“…[72] Treatmento f140 a with one equivalent of the sterically encumbered silylene Roesky and co-workersa lso studied the reaction of 140 a toward related low valent aluminiumc ompounds. [73] As mentioned in section2.4.3 (Scheme 20), Scheer and coworkers have demonstrated that the N-heterocyclicc arbene 1,3,4,5-tetramethylimidazol-2-ylidene (NHC) is av aluable reagent for the contraction of a cyclo-P 4 ring. [63] In the same work, this concept was also appliedt ot he early transitionmetal triple-decker sandwich complexes [(Cp*M) 2 (m,h 6 :h 6 -P 6 )] (152,M = V, Mo, Scheme 26).…”
Section: Functionalization Of P N Ligands (N ! 5)mentioning
confidence: 99%
“… 14,15,23 Indeed, the major drawback of the so far used strategies is their immensely limited applicability to a very narrow range of electrophile/nucleophile combinations. This is usually reflected in the use of rather exotic low-valent main group species such as tetrylenes, 14 b ,18 {Cp*Al} 4 , 24 or the utilization of highly reactive, e.g. anionic, polyphosphorus ligand complexes.…”
Section: Introductionmentioning
confidence: 99%